Canopy occupation volume as an indicator of canopy photosynthetic capacity. Issue 2 (3rd August 2021) - Liu, Fusang; Song, Qingfeng; Zhao, Jinke; Mao, Linxiong; Bu, Hongyi; Hu, Yong; Zhu, Xin‐Guang
Summary: Leaf angle and leaf area index together influence canopy light interception and canopy photosynthesis. However, so far, there is no effective method to identify the optimal combination of these two parameters for canopy photosynthesis. In this study, first a robust high‐throughput method for accurate segmentation of maize organs based on 3D point clouds data was developed, then the segmented plant organs were used to generate new 3D point clouds for the canopy of altered architectures. With this, we simulated the synergistic effect of leaf area and leaf angle on canopy photosynthesis. The results show that, compared to the traditional parameters describing the canopy photosynthesis including leaf area index, facet angle and canopy coverage, a new parameter – the canopy occupation volume (COV) – can better explain the variations of canopy photosynthetic capacity. Specifically, COV can explain > 79% variations of canopy photosynthesis generated by changing leaf angle and > 84% variations of canopy photosynthesis generated by changing leaf area. As COV can be calculated in a high‐throughput manner based on the canopy point clouds, it can be used to evaluate canopy architecture in breeding and agronomic research.